Teks Ucapan Yang Hormat Profesor Dato’ Dr. Daing Nasir Ibrahim Naib Canselor Universiti Malaysia Pahang Sempena Memorandum of Agreement Signing Ceremony between UMP and Polytechnic College of Hebei University of Science & Technology - Pejabat, Naib Canselor UMP (Universiti Malaysia Pahang, 2016)
t is indeed a great pleasure that I have the honour of welcoming all of you this afternoon, and I would like to extend my warmest greetings to our special guests from the Polytechnic College of Hebei University of Science and Technology (PCHEBUST) and Hebei Science and Technology University who have travelled all the way from the People’s Republic of China for this momentous occasion.